The effect of financial education in the family and self-control on family financial management behavior with financial literacy as moderating: Study on families in Sikka Regency, East Nusa Tenggara - Dewi, Eugenia Sartini Mega; Wiagustini, Ni Luh Putu (International research journal of management, IT and social sciences, 2025)
This study aims to analyze the effect of financial education in the family, self-control, and financial literacy on family financial management behavior, with financial literacy as a moderator in the midst of the phenomenon of the high cost of traditional weddings and the consumptive lifestyle in Sikka Regency, East Nusa Tenggara. The research method used is quantitative. The sample used was 140 respondents determined by a purposive sampling technique. The research instrument used is a questionnaire distributed offline and online to respondents who are heads of families or family members who are responsible for managing family finances. The data will be analyzed using the Structural Equation Model (SEM) statistical analysis with the help of SmartPLS software. The results of the analysis show that financial education in the family and self-control have a significant positive effect on family financial management behavior. Financial literacy has a significant positive effect on family financial management behavior and is proven to strengthen the influence of financial education in the family and self-control on family financial management behavior.